Mitigación del impacto ambiental en el sector bananero con la implementación de drones para la aerotomización - Quirola León, Giovanny Stevens (2017)
The present research focuses on the study of the environmental impact mitigation in the banana sector with the deployment of drones for the aerotomizacion. It was determined as a main objective is to analyze and quantify the environmental impact produced with the use of drones for the aerotomizacion in the cultivation of bananas within the association of producers "Aso Guabo". In this way, was established as specific objectives refer to the level of information on unmanned aerial vehicles (drones) in the Association of Producers of the Guabo; To assess the potential benefits that can be generated with the deployment of drones for the atomization in bananas; and, to compare the prices of the service between traditional atomization and carried out by unmanned aerial vehicles (drones). Within the theoretical epistemological study discussed issues related to the environmental impact of the aerotomizaciones in the banana sector, on the factors of water pollution, contamination of surrounding areas and sound pollution. In addition is spelled out on transfers of technology in the agricultural sector, the aerotomizacion, the characteristics of the traditional agricultural aircraft, damage to health because of the aerotomizacion, the environmental mitigation, the combustion air in agriculture, precision agriculture, unmanned aerial vehicles (uavs), the application of drones in agriculture and finally the advantages in the use of drones for agriculture. The research is non-experimental, descriptive, narrative, explanatory, with qualitative and quantitative characteristics. Applied survey, with their respective questionnaires of open and closed questions. It is exploratory with the purpose of delimiting the problem of health impact that causes improper dispersion of pesticides from the air. It is concluded that in the agricultural environment, there is already a partial knowledge on the new technologies that can help improve productivity as well as reduce the environmental impacts, the drones are part of the technological changes. However, the information is limited with respect to pest control through the system of multispectral photographs in drones that can benefit for a better control of the productivity. The main environmental factors affected demonstrating greater incidence with the use of airplanes are job security, public health and surface waters, considered according to the Leopold matrix as highly significant, however with the use of drones these impact levels are reduced to a degree of fairly significant. In the same way we evaluated the activities which are in a range highly significant and fairly significant including the atomization in flight, downloads of remnants and cleanliness of empty containers, as well as these levels are reduced with the use of drones making it one of an important tool to reduce the environmental impact and make a more efficient aerotomizacion. The percentage difference between one or the other alternatives of aeroatomizacion in the banana plantations is slightly significant, it is as well that the drones allows a reduction of costs for the producer and that this is going to have higher incidence in plantations with scale productions, in which the greater volume of consumption of inputs will reduce costs.